SEJARAH PERKEMBANGAN BUNRAKU (WAYANG GOLEK ALA JEPANG) - Tri Mulyani Wahyuningsih (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2007)
: Bunraku is one of Japanese puppet arts. Bunraku uses of Â¾ of adult size puppet played by three people. Puppet is originally used for god and goddess admiration in temples. When people began to use the puppet outside the temple, it began to be used as a medium of entertainment. The puppet is originally named Heike â€“ Biwa before it was changed into Ningyou Joururi and finally called Bunraku up till now.